Investigation of the Genotoxicity of Malathion to Grass Carp (Ctenopharyngodon idella) Using Comet Assay - khan, Fida Ullah; Ullah Khan, Ahmad; Ahmad lodhi, Faisal; khan, Wasibullah; Khalid , Meraj (Indus Journal of Bioscience Research, 2024)
Malathion, an organophosphorus insecticide, used around the world, can be harmful to the environment because it doesn’t break down easily, especially in aquatic ecosystems. As it accumulates in these environments, it can cause serious damage, disrupting biodiversity and harming water quality. This study assessed the genotoxic effects of malathion on the blood cells of grass carp (Ctenopharyngodon idella). Firstly, the LC50 value of malathion for 96 hours’ exposure was identified to be 2.42 ppm. The fish were then subjected to three varying concentrations of malathion: 0.403 ppm/day, 0.605 ppm/day, and 1.21 ppm/day, over periods of 10, 20, and 30 days. The control group remained unexposed to malathion. The results indicated that DNA damage was significant across all concentrations after 10 days (P < 0.05). Moreover, after 20 and 30 days of trials, the extent of DNA damage exhibited a markedly significant increase (P < 0.000).The comet assay was used to evaluate the extent of DNA damage in the fish, taking into account exposure time and dosage. Our results show that higher concentrations and longer exposures aggravated DNA damage. Authorities must regulate and monitor the inappropriate use of malathion, as this study demonstrated its significant genotoxic effects on Ctenopharyngodon idella.